The Role of Ustadzah in Improving the Akhlakul Karimah of Students Class 5 at Ibtida'iyah Madrasah Islamiyah Darul Falah - Mufti, Raviqha; Irhamuddin, Irhamuddin; Ehwanudin, Ehwanudin (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
Akhlakul Karimah is one of the fundamental aspects of Islamic education that must be instilled from an early age, in the world of education, especially in the madrasa environment. In this context, the ustadzah has a very important role in guiding, directing and instilling moral values in the students. The role of the ustadzah in improving the morals of the students is very much needed in the Islamic madrasah